The innate immune sensor LGP2 activates antiviral signaling by regulating MDA5-RNA interaction and filament assembly - Bruns, Annie M. (2014)
Cytoplasmic pattern recognition receptors detect non-self RNAs during virus infections and initiate antiviral signaling. One receptor, MDA5, possesses essential signaling domains, but weak RNA binding. A second receptor, LGP2, rapidly detects diverse dsRNA species, but lacks signaling domains. Accumulating evidence suggests LGP2 and MDA5 work together to detect viral RNA and generate a complete antiviral response, but the basis for their cooperation has been elusive. Experiments presented here address this gap in antiviral signaling, revealing that LGP2 assists MDA5-RNA interactions leading to enhanced MDA5-mediated antiviral signaling. LGP2 increases the initial rate of MDA5-RNA interaction and regulates MDA5 filament assembly, resulting in the formation of more numerous, shorter MDA5 filaments that are shown to generate equivalent or greater signaling activity in vivo than the longer filaments containing only MDA5. These findings provide a mechanism for LGP2 co-activation of MDA5 and a biological context for MDA5-RNA filaments in antiviral responses.